Towards a New LLL Paradigm? EU Policy on Key Competences and Reskilling: Facets and Trends - N. Papadakis (University of Sofia, 2009)
Policy initiatives such as the European Year of Creativity and Innovation (2009) and the EU Framework on "Key Competences" (2006 and onwards) aim at contributing on the ongoing reconceptualisation of skills (gradually correlated to Reskilling, Employability, Sustainability and Competitiveness) and operate within the context of a changing balance between technocracy, pedagogy and politics. I.e. according to the EU cluster on Key Competences "major themes are applied throughout the Framework: creativity, critical thinking, initiative taking, play a major role in all eight key competences". This explicit changing role of Creativity gains in political visibility and requires a contextually embedded and multidisciplinary approach. On such a perspective the present paper analyzes the political context and interest politics' impact on the transformations on LLL and reskilling within the EU policy agenda and raises methodological and epistemological issues on the interface between educational and policy analysis.